Bentuk-Bentuk Kekerasan Domestik Dan Permasalahannya (Studi Perbandingan Hukum Indonesia dan Malaysia) - -, Kuswardani (UI Scholars Hub, 2017)
The paper is purposed to describe / explain criminal laws which regulate domestic violence and the problems happen in Indonesia. This study uses the comparison method which compare substance criminal law of Indonesia with criminal law of Malaysia. The study is focused in the subject matter from criminal law of substantive. The result point out that both of the two countries have had criminal law on domestic violence, Indonesia is regulated at The Act of Elimination of Domestic Violence No 23 of 2004, while Malaysia is appointed at Domestic Violence 1994, and this was amendment on February 20, 2012. This concise comparison can be as a material of criminal law reform